1978
DOI: 10.1111/j.1600-0447.1978.tb06906.x
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive‐compulsive neurosis, anacastic symptomatology and ABO blood types

Abstract: Determinations of ABO blood types was carried out in 38 patients with obsessive-compulsive neurosis, 48 schizophrenics with anancastic symptomatology, 31 depressives with anancastic symptomatology, 260 schizophrenics free of anancastic symptomatology and 65 depressives free of anancastic symptomatology. Results were compared with a representative sample of the general population. The findings of the present study provide evidence of an association between obsessive-compulsive neurosis and phenotype A, whilst a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…It was shown in a previous study that obses sive-compulsive patients, compared to a re presentative sample of the general population, are characterized by a higher incidence of phenotype A and a lower incidence of pheno type O (3). In view of a close association between obsessive-compulsive neurosis and obsessional personality (4), it was thought that the possibility of an association between obses sional personality and ABO blood types merits an investigation.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown in a previous study that obses sive-compulsive patients, compared to a re presentative sample of the general population, are characterized by a higher incidence of phenotype A and a lower incidence of pheno type O (3). In view of a close association between obsessive-compulsive neurosis and obsessional personality (4), it was thought that the possibility of an association between obses sional personality and ABO blood types merits an investigation.…”
Section: Introductionmentioning
confidence: 99%
“…22 Rinieris et al suggested that patients with either obsessive-compulsive neurosis or hysteria demonstrate a higher incidence of blood phenotype A and a lower incidence of blood phenotype O, as compared to a representative sample of the general population. 23,24 Also, in another study Rinieris et al demonstrated a greater incidence of obsessional personality traits in blood groups A, B and AB than in Blood Group O using 600 participants. The researchers determined that blood group O might be associated with personality traits hindering the development of obsessive-compulsive symptomology.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with several previous reports. In two studies of Greek patients with obsessivecompulsive disorder Rinieris and co-workers find the frequency of blood type O is significantly lower, and that of blood type A is significantly higher, than in the general population [Rinieris et al" 1978[Rinieris et al" , 1983. They also report that blood type O occurs significantly less often than expected among normal persons with obsessional per sonality traits, while blood type A is more common than expected, although not significantly [Rinieris et al" 1980], They suggest that blood type O is associated with factors which protect against the development of obses sive-compulsive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of blood groups in psychiatric dis ease suggest that type A is over-represented in schizo phrenia [Masters, 1967;Czechowicz and Pamnany, 1972;Mendlewicz et al, 1974] and obsessive-compul sive disorder [Rinieris et al, 1978[Rinieris et al, , 1983. Blood type O occurs more often than expected in bipolar illness [Mendlewicz et al, 1974;Parker et al, 1961;Shapiro et al, 1977] and less often in both obsessive-compulsive disorder [Rinieris et al, 1978[Rinieris et al, , 1983 and in individuals with obsessive-compulsive traits [Rinieris et al, 1980], Not all studies find differences according to blood group, however [McKeon and McColl, 1982], A problem with many of these studies is that a large number of statistical tests are performed on data from a single patient sample, which may produce a significant finding by chance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation